1999
DOI: 10.1271/bbb.63.1512
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Blue Pigment Formed in a D-Xylose-Glycine Reaction System

Abstract: D-Xylose (1 M), glycine (0.1 M), and sodium hydrogencarbonate (0.1 M) were dissolved in aqueous 60% ethanol at pH 8.1 and left at 26.5°C for 2 days in a dark room under nitrogen displacement. Blue pigment was isolated and purified from the blue solution by anionic exchange and gel filtration chromatographies. Blue pigment which was designated Blue-M1 (blue Maillard reaction intermediate-1) was identified as 5-{[1,4-(dicarboxymethyl)-5-(2,3-dihydroxypropyl)-2-pyrrolo[3,2-b]pyrrolyl]methine}-1,4-(dicarboxymethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
35
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 7 publications
0
35
0
Order By: Relevance
“…1) Miura and Gomyo, 2) and Gomyo et al, 3) have found the formation of blue pigments in the Maillard reaction of D-xylose and glycine under anaerobic conditions. Hayase et al 4) reported that a blue pigment was isolated and identified…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1) Miura and Gomyo, 2) and Gomyo et al, 3) have found the formation of blue pigments in the Maillard reaction of D-xylose and glycine under anaerobic conditions. Hayase et al 4) reported that a blue pigment was isolated and identified…”
mentioning
confidence: 99%
“…4) Briefly, D-xylose (1 M), glycine (0.1 M) and sodium hydrogen carbonate (0.1 M) were dissolved in 1 liter of aqueous 60% ethanol, and the solution adjusted to pH 8.1 with HCl. The reaction mixture was placed in a nitrogen atmosphere and incubated at 26.5 C for 2 days, and 2 C for 4 days in a dark place.…”
mentioning
confidence: 99%
“…Although several colored reaction products of pentose [5][6][7][8][9] and its decomposed products, including furfural, [10][11][12][13] have been reported to date, far fewer data on the reaction products of pentose and furfural are available than those of hexose, especially glucose, and its decomposed products.…”
mentioning
confidence: 99%
“…2) Miura and Gomyo 3) and Gomyo et al 4) have found the formation of colored compounds in the Maillard reaction between D-xylose and glycine. Our group [5][6][7] has reported the identification of novel blue pigments designated Blue-M1 (blue Maillard intermediate-1, Fig. 1) and Blue-M2.…”
mentioning
confidence: 99%